Учебный текст как основа развития иноязычных коммуникативных навыков и грамматических навыков студентов экономических ВУЗов - Бочкарёва, Т.В.; Клюева, В.Г. (Культура народов Причерноморья, 2013)
В статье анализируются основные требования, предъявляемые к текстам на английском для студентов, изучающих экономику, как к учебным материалам, способствующим развитию коммуникативных иноязычных навыков и навыков употребления грамматических конструкций. Предлагаются примеры заданий, которые могут быть использованы при работе с текстом и вызывающие интерес к процессу обучения. Подчёркивается важность текста как необходимого компонента любого учебного пособия. В статті аналізуються основні вимоги, які пред’являються до текстів англійською мовою для студентів економічних факультетів як до навчальних матеріалів, які сприяють розвитку комунікативних іньшомовних навиків та навиків застосування граматичних конструкцій. Пропонуються приклади завдань, які можуть бути використані під час роботи з текстом та які викликають інтерес до навчального процесу. Наголошується на важливість тексту як необхідного компоненту будь – якого навчального посібника. The basic requirements set to texts as to educational materials that help develop communicative and grammar skills are being analyzed in the article. Examples of tasks that can be used in the process of working with a text and that arouse interest to the educational process are given here. The importance of text as a necessary component of any textbook is emphasized in the work. Different lexical material that must be included into educational texts is studied in the article. The article runs that texts for beginners must be shorter and easier than texts for students that have been studying foreign languages for a longer period if time. The quantity of unknown words cannot exceed 10-15 %. It is extremely important for students to learn new words and to study new grammar structures when they work with texts. The following exercises are proposed: choosing a title, making a plan, dividing a text into segments, looking for key words, giving one’s own opinion, making dialogues based on the material of the text. Writing an annotation is one of the most important and difficult tasks. It shows high level of a language command because students are able to analyze the main ideas of texts that they study. Three types of educational texts are enumerated in the article: the first type is the text invented by authors of a textbook; the second is authentic text that shows specific features of science, culture or economy of the country where the text has been written; the third is the educational text that is based on an authentic one but has been adopted to meet requirements of a University program and combines advantages of educational and authentic texts. That is why the last one is the most effective. The authors of the article want to stress that mastering a language is based on special skills that educational texts help develop. The problem set in the text must contribute to the development of logical thinking of young people.